Magic mushrooms and mood: exploring Psilocybin as a depression treatment - Rasool, Maria; Hannan, Taha Muhammad; Imam, Muhammad (Journal of the Pakistan Medical Association, 2025)
Dear Editor, In view of ongoing global research on mental health, especially Major Depressive Disorder, we would like to draw attention to a psychedelic substance, Psilocybin, which has been emerging as a viable treatment option for MDD. Psilocybin is a psychedelic compound derived from certain mushrooms that acts on Serotonergic receptors (primarily 5HT-2A). Psychedelic substances have psychological effects, i.e., hallucinations, euphoria, and altered perception (1). Studies have demonstrated their effectiveness in the treatment of disorders like ‘Major Depressive Disorder (MDD)’, and ‘Treatment-Resistant Depression’. Recently, the FDA gave ‘breakthrough’ therapy status to a psilocybin treatment developed by London-based biotechnology company ‘Compass Pathways Ltd’ as stated in (2).